BIOLOGICAL PROPERTIES OF RHOPALOSIPHUM PADI LINN. IN TWO HABITATS WITH DIFFERENT CLIMATE REGIMS - Yonny Koesmaryono; Tetsuya Haseba (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1993)
Abstract is available in the full text (pdf format)